Automated Operational Modal Analysis of an arch bridge considering the influence of the parametric methods inputs. (2017) - Marrongelli, Gabriele; Magalhães, Filipe; Cunha, Álvaro
Abstract: This paper presents a strategy to efficiently obtain modal parameters estimates with parametric methods using a set of values for their input parameters. This is illustrated in detail with the application of the SSI-COV method, by the construction of tri-dimensional stabilization diagrams that consider varying modal orders and varying lengths for the correlation matrices, which are then automatically analyzed using clustering techniques. As case study, it is used an arch bridge built in 1940 with an 80 meter long non-reinforced concrete arch. The developed routines are applied to the datasets collected during a quite extensive ambient vibration test. The work also highlights how the natural frequencies and more particularly the modal damping values may depend on the choice of the parametric method input parameters.